DHEAS and Human Development: An Evolutionary Perspective - Campbell, Benjamin (Frontiers in Endocrinology, 2020)
Adrenarche, the post-natal rise of DHEA and DHEAS is unique to humans and the African Apes. Recent findings have linked DHEA in humans to the development of the left dorsolateral prefrontal cortex (lDPFC) between the ages of 4 to 8 years and the right temporoparietal junction (rTPJ) from 7 to 12 years of age. Given the association of the lDLPFC with the 5-to-8 transition and the rTPJ with mentalizing during middle childhood DHEA may have played an important role in the evolution of the human brain. I argue that increasing protein in the diet over the course of human evolution not only increased levels of DHEAS, but linked meat consumption with brain development during the important 5- to-8 transition. Consumption of animal protein has been associated with IGF-1, implicated in the development of the adrenal zona reticularis (ZR), the site of DHEAS production. In humans and chimps, the zona reticularis emerges at 3-4 years. For chimps this coincides with weaning and peak synaptogenesis. Among human subsistence populations, weaning is completed around 2 ½ years, while synaptogenesis peaks around 5 years. Thus in chimpanzees, early cortical maturation is tied to the mother; in humans it may be associated with post-weaning provisioning by others. I call for further research on adrenarche among the African apes as a critical comparison to humans. In addition, I suggest research in subsistence populations to establish the role of energetics in the timing of adrenarche and its association with the onset of middle childhood.